1999
DOI: 10.1007/s001250051223
|View full text |Cite
|
Sign up to set email alerts
|

Only limited effects of aminoguanidine treatment on peripheral nerve function, (Na + ,K + )-ATPase activity and thrombomodulin expression in streptozotocin-induced diabetic rats

Abstract: Inhibition of glycation by use of anti-glycation agents like aminoguanidine is now regarded as a promising new way for the prevention and treatment of vascular and neuropathic complications in diabetes [1,2]. Several laboratories have reported beneficial effects of aminoguanidine on peripheral nerve function in experimental models of diabetic neuropathy [3±5]. In these studies, the aminoguanidine effects were accompanied by an improvement in nerve blood flow [3,4] and reduction of advanced glycation end produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…Hence, this animal model does not establish whether diabetes or its treatment is related to altered TM expression in nerve microvasculature (33). These findings must be interpreted with caution because streptozoticin-induced diabetes may differ from human diabetic neuropathy in its time course and biological mechanisms.…”
Section: Diabetes Vol 51 June 2002mentioning
confidence: 87%
“…Hence, this animal model does not establish whether diabetes or its treatment is related to altered TM expression in nerve microvasculature (33). These findings must be interpreted with caution because streptozoticin-induced diabetes may differ from human diabetic neuropathy in its time course and biological mechanisms.…”
Section: Diabetes Vol 51 June 2002mentioning
confidence: 87%
“…Its effects on nerve morphometry have not been assessed at this stage because aminoguanidine treated animals have not reached the duration of diabetes for nerve biopsies electrophysiological results lead us, however, to believe that aminoguanidine will have little it any effect on structural changes. The inability of aminoguanidine to restore nerve function in baboons differs from some of the studies in rats that showed treatment to be beneficial although the results are conflicting [18,19,22,41,42]. One study found that diabetic rats given 50 mg/kg aminoguanidine in the drinking water for 16 weeks had NCV restored although doses of 10 and 25 mg/ kg were ineffective [19].…”
Section: Discussionmentioning
confidence: 99%
“…1). Short-term treatment with aminoguanidine ameliorates the NCV and the Na + /K + -ATPase defects, but not endothelial damage as reflected by systemic thrombomodulin concentrations [111]. On the other hand, long-term aminoguanidine treatment has beneficial effects on the structural alterations of endoneurial microvessels in the STZ rat [112].…”
Section: Non-enzymatic Glycation and Oxidative Stressmentioning
confidence: 97%